2020
DOI: 10.21203/rs.3.rs-29176/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolated Maternal Hypothyroxinemia and Adverse Pregnancy Outcomes: A Systematic Review

Abstract: Abstract Background Maternal thyroid hormones are vital for a normal pregnancy and the development of fetus and childhood; inadequate availability of thyroid hormones during pregnancy is associated with adverse pregnancy outcomes. This systematic review aimed to investigate the association between Isolated Maternal hypothyroxinemia (IMH) and adverse pregnancy outcomes. Method: PubMed, Scopus and Web of science were searched for retrieving observational studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The association was shown in the patients with IMH either in the 1st or the 2nd trimester of preg nancy. In other studies, no associations were reported between IMH and GDM [8,[18][19][20][21]. In one study analyzing IMH both in the 1st and 2nd trimester of pregnancy, IMH was found not to be asso ciated with GDM [12].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The association was shown in the patients with IMH either in the 1st or the 2nd trimester of preg nancy. In other studies, no associations were reported between IMH and GDM [8,[18][19][20][21]. In one study analyzing IMH both in the 1st and 2nd trimester of pregnancy, IMH was found not to be asso ciated with GDM [12].…”
Section: Discussionmentioning
confidence: 89%
“…IMH may be associated with preterm birth, macrosomia, neonatal intraventricular hemor rhage, and poorer neuropsychological development in the offspring [14,15]. IMH was found to be associated also with an increased risk of GDM in some studies [8,16,17]. The association was shown in the patients with IMH either in the 1st or the 2nd trimester of preg nancy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations